Prevention of Postpartum Traumatic Stress in Mothers with Preterm Infants: Manual Development and Evaluation. (1st August 2013) - Shaw, Richard J.; Sweester, Carrie J.; St. John, Nicholas; Lilo, Emily; Corcoran, Julia B.; Jo, Booil; Howell, Shelley H.K.; Benitz, William E.; Feinstein, Nancy; Melnyk, Bernadette; Horwitz, Sarah M.
Abstract : Premature birth has been associated with multiple adverse maternal psychological outcomes that include depression, anxiety, and trauma as well as adverse effects on maternal coping ability and parenting style. Infants who are premature are more likely to have poorer cognitive and developmental functioning and, thus, may be harder to parent, both as infants and as they get older. In response to these findings, a number of educational and behavioral interventions have been developed that target maternal psychological functioning, parenting, and aspects of the parent-infant relationship. The current study aimed to both develop and evaluate a treatment that integrates, for the first time, effective interventions for reducing symptoms of posttraumatic stress disorder (PTSD) and enhancing maternal-infant interactions. Conclusions from the study indicate that the intervention is feasible, able to be implemented with a high level of fidelity, and is rated as highly satisfactory by participants. Though encouraging, these findings are preliminary, and future studies should strive to reproduce these findings with a larger sample size and a comparison group.